2004
DOI: 10.1128/jcm.42.6.2663-2667.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Three Serological Methods for Detection of Human Herpesvirus 8-Specific Antibodies in Canadian Allogeneic Stem Cell Transplant Recipients

Abstract: Human herpesvirus 8 (HHV-8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Of them three were negative for HHV-8 antibody, one was positive. HHV-8 DNA is rarely detected in plasma, serum, or buffy coat samples from individuals without KS [12,[17][18][19].…”
Section: Of Hhv-8 Infection In Pulmonary Tb Patients Is Lower Than Thmentioning
confidence: 96%
“…Of them three were negative for HHV-8 antibody, one was positive. HHV-8 DNA is rarely detected in plasma, serum, or buffy coat samples from individuals without KS [12,[17][18][19].…”
Section: Of Hhv-8 Infection In Pulmonary Tb Patients Is Lower Than Thmentioning
confidence: 96%
“…These include open reading frame (ORF) proteins 6,8,9,25,26,39,59, 65, 68, and 73; K8.1A; and K8.1B (5). Of these proteins, ORF59, K8.1A, ORF65, and ORF73 have been used in the development of various enzyme immunoassays (EIAs) and have been reported to be good candidate antigens (5,14,16,19,28,32). There are now two commercially available EIAs that use whole-virus lysate and synthetic peptides.…”
Section: Human Herpesvirus 8 (Hhv-8) or Kaposi's Sarcoma (Ks)-associmentioning
confidence: 99%
“…Large studies in the USA showed a seroprevalence of 0.5-7 % among the general population [ 130 , 153 , 219 , 319 ]. The prevalence in Canada has been documented by studies on transplant recipients, showing 0-2 % seropositivity before transplantation [ 364 ]. Cases of classic KS reported in Inuit people living in northern Quebec may indicate that KSHV is more diffuse in this population [ 348 ], although seroprevalence data are not yet available.…”
Section: Epidemiology Of Kshv Infectionmentioning
confidence: 97%